Crop Performance, Soil Moisture and Quality Parameters in Bt Cotton as Influenced by Mulching and Nutrient Management Practices - SHIROL, MALLIKARJUN C.; SUDHA, T.; ANGADI, S. S. (Cotton Research Journal, 2021)
A field experiment was conducted in a split plot design during the rainy (kharif) season of 2013 at Dharwad, Karnataka, to study the effect of mulching and nutrient management practices on crop performance and quality parameters in Bt Cotton. Mulching with cotton stalks@10t/ha and RDF+B@5kg/ha+Zn@10kg/ha recorded significantly higher number of sympodial branches/plant, total number of bolis/plant, boll weight and seed cotton yield over no mulch+RDF alone. Application of RDF+B @5kg/ha +Zn @10kg/ha recorded higher ginning percentage over no mulching.